1999
DOI: 10.1046/j.1365-2672.1999.00712.x
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation into the differences between the Bioscreen and the traditional plate count disinfectant test methods

Abstract: Investigations of biocide efficacy by automated methods involving optical density measurements, e.g. using the recently published 'Bioscreen' method, are complicated by the fact that a poor correlation often exists between the log reductions obtained using the automated method vs those obtained by the traditional plate count methods. It was hypothesized that the differences observed between the two methods were due to the level of cell injury, which was masked by the optical density methods but which was recog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…increased sensitivity. The FB community in thick juice did not change upon addition of hop components, as was confirmed by preliminary identification of 18 isolates, but may have become stressed by exposure to the hop extract which may explain the delayed colony formation upon plating (Lambert and van der Ouderaa 1999). Although selection for resistance to hop components has been reported (Haas and Barsoumian 1994; Larson et al.…”
Section: Discussionmentioning
confidence: 76%
“…increased sensitivity. The FB community in thick juice did not change upon addition of hop components, as was confirmed by preliminary identification of 18 isolates, but may have become stressed by exposure to the hop extract which may explain the delayed colony formation upon plating (Lambert and van der Ouderaa 1999). Although selection for resistance to hop components has been reported (Haas and Barsoumian 1994; Larson et al.…”
Section: Discussionmentioning
confidence: 76%
“…1995), but these are labour intensive, generally require that particular reporter constructs are available or are variable in their outcome. Another option is to submerge the test pieces, post‐treatment, and to measure the recovery of the surviving cells either by turbidometric (Lambert and van der Ouderaa 1999; Lambert et al . 1999) or conductimetric (Connolly et al .…”
Section: Introductionmentioning
confidence: 99%
“…A number of direct observation methodologies have been described that employ vital staining (Wood et al 1998), ATP-levels (Kinniment andWimpenny 1992;Jakubovics and Dow 1997), or reporter genes, such as Lux, for cellular vitality (Walker et al 1992;Duffy et al 1995), but these are labour intensive, generally require that particular reporter constructs are available or are variable in their outcome. Another option is to submerge the test pieces, post-treatment, and to measure the recovery of the surviving cells either by turbidometric (Lambert and van der Ouderaa 1999; or conductimetric (Connolly et al 1994;Johnston and Jones 1995) methods. In the present study we have developed a turbidity endpoint method that is suitable for the generation of kinetic data describing the disinfection of bio®lms.…”
Section: Introductionmentioning
confidence: 99%
“…Lambert and others (1998) hypothesized that the OD (Bioscreen) method does not account for injured cells the same as using plate count methods, thus leading to an overestimation of the results. In a subsequent study, Lambert concluded that increasing the concentration of test compounds or time of exposure led to a reduction in colony size on the plate for Staphylococcus aureus cells (Lambert and van der Ouderaa 1999). It was suggested in the Lambert and van der Ouderaa (1999) study that the smaller colonies on the plate originated from injured cells that needed to recover before multiplying, and therefore did not have as much time to reach the size of healthy colonies.…”
Section: Resultsmentioning
confidence: 99%
“…In a subsequent study, Lambert concluded that increasing the concentration of test compounds or time of exposure led to a reduction in colony size on the plate for Staphylococcus aureus cells (Lambert and van der Ouderaa 1999). It was suggested in the Lambert and van der Ouderaa (1999) study that the smaller colonies on the plate originated from injured cells that needed to recover before multiplying, and therefore did not have as much time to reach the size of healthy colonies. As expected, smaller cells will affect OD less than larger, healthy colonies.…”
Section: Resultsmentioning
confidence: 99%